An Analysis Study on the Effect of the Use of Electronic Medical Records on the Effectiveness and Efficiency of Services at Public Health Centers (Puskesmas) in Indonesia: A Systematic Review - Nathan, Daniel Setiawan; Rostiaty, Erti (The International Journal of Medical Science and Health Research, 2024)
Background: EMR utilize electronic systems to store, manage, and share patient health information more efficiently and accurately. Given the importance of using EMR in improving the quality and efficiency of health services in Indonesia, this study aims to systematically review the existing evidence related to the effectiveness of EMR implementation on the effectiveness and efficiency of services at Puskesmas in Indonesia. This study follows the PRISMA 2020 standard, examining English literature from 2014 to 2024. The study excluded editorials, reviews from the same journal, and submissions without DOI. PubMed, SagePub, SpringerLink, and Google Scholar are used as literary sources. Results: Initially getting 360 articles from online databases (PubMed, SagePub, SpringerLink, and Google Scholar), eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusion: Overall, the use of Electronic Medical Records at primary healthcare in Indonesia provides many advantages in terms of the effectiveness and efficiency of health services, especially in accelerating queue waiting time, registration, service in the police, and drug taking. However, to achieve optimal implementation, efforts to improve technology infrastructure, training for health workers, and good network management are needed to overcome technical obstacles and ensure smooth service flow at the primary healthcare.